1991
DOI: 10.1007/bf01913110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sample particle size and heating rate on the thermal decomposition of K2C2O4

Abstract: The thermal decomposition of K2C204 in a current of dry nitrogen according to the reaction K2C204 "* K2CO3 + CO (1) is shown to be influenced profoundly by the sample particle size and the heating rate. For finely ground samples, a lower activation energy (Ea = 255.15+ 5 kJ mo1-1) is obtained as compared with the 312.6 -4-6 kJ mo1-1 observed for crystal chips weighing 30-40 rag. The characteristic temperatures (the reaction start, peak and end temperatures) are markedly reduced by fine grinding. High heating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the researches of the decomposition thermodynamics, some researchers reported the size dependence of decomposition temperatures of nanomaterials, and found that the decomposition temperatures are related to the corresponding particle sizes whereby the decomposition temperatures decrease with the decrease of particle sizes (Mulokozi and Lugwisha 1991;Markmaitree et al 2006;Sovizi et al 2009;Fathollahi et al 2008;Wang et al 2014a, b). And some other researchers reported the thermodynamic functions for decomposition reaction of nanomaterials with single particle size (Bhakta et al 2012;Harutyunyan et al 2009;Paskevicius et al 2010), and compared the decomposition reaction enthalpy with that of the bulk counterparts (Paskevicius et al 2010), and found that there is a small but measurable decrease.…”
Section: Introductionmentioning
confidence: 99%
“…In the researches of the decomposition thermodynamics, some researchers reported the size dependence of decomposition temperatures of nanomaterials, and found that the decomposition temperatures are related to the corresponding particle sizes whereby the decomposition temperatures decrease with the decrease of particle sizes (Mulokozi and Lugwisha 1991;Markmaitree et al 2006;Sovizi et al 2009;Fathollahi et al 2008;Wang et al 2014a, b). And some other researchers reported the thermodynamic functions for decomposition reaction of nanomaterials with single particle size (Bhakta et al 2012;Harutyunyan et al 2009;Paskevicius et al 2010), and compared the decomposition reaction enthalpy with that of the bulk counterparts (Paskevicius et al 2010), and found that there is a small but measurable decrease.…”
Section: Introductionmentioning
confidence: 99%